Intensive out-of-hospital coaching for frequently hospitalized COPD patients: a before-after feasibility study - Noort, Bart A. C.; van der Vaart, Taco; van der Maten, Jan; Metting, Esther; Ahaus, Kees (Frontiers in Medicine, 2023)
1.1 Background This study assesses whether out-of-hospital coaching of re-hospitalized, severe COPD patients by specialized respiratory nurses is feasible in terms of cost-effectiveness, implementation, and recipient acceptability. The coaching was aimed at improving patients’ health management abilities, motivation for healthy behavior, strengthening the professional and informal care network, stimulating physiotherapy treatment and exercise training, improving knowledge on symptom recognition and medication use, and providing safety and support. 1.2 Methods Cost-effectiveness of six months of out-of-hospital coaching was assessed based on a before-after intervention design, with real-life data and one-year follow-up. 170 patients were included. Primary (questionnaires, meeting reports) and secondary data (insurance reimbursement data) were collected in one province in the Netherlands. The implementing and recipient acceptability was assessed based on the number of successfully delivered coaching sessions, questionnaire response rate, Patient Reported Experience Measure, and interviews with coaches. 1.3 Results Post-intervention, the COPD-related hospitalization rate was reduced by 24%, and patients improved in terms of health status, anxiety, and nutritional status. Patients with a high mental burden and a poor score for health impairment and well-being at the start of the intervention showed the greatest reduction in hospitalizations. The coaching service was successfully implemented and considered acceptable by recipients, based on patient and coach satisfaction and clinical use of patient-reported measures. 1.4 Conclusions The study demonstrates the value of coaching patients out-of-hospital, with a strong link to primary care, but with support of hospital expertise, thereby adding to previous studies on disease- or self-management support in either primary or secondary care settings. Patients benefit from personal attention, practical advice, exercise training, and motivational meetings, thereby improving health status and reducing the likelihood of re-hospitalization and its associated costs.